Choosing Health and the inner citadel. Issue 1 (22nd December 2005) - Allmark, P
Abstract : It is argued in this paper that the latest UK government white paper on public health, Choosing Health, is vulnerable to a charge of paternalism. For some years libertarians have levelled this charge at public health policies. The white paper tries to avoid it by constant reference to informed choice and choice related terms. The implication is that the government aims only to inform the public of health issues; how they respond is up to them. It is argued here, however, that underlying the notion of informed choice is a Kantian, "inner citadel" view of autonomy. According to this view, each of us acts autonomously only when we act in accord with reason. On such a view it is possible to justify coercing, cajoling, and conning people on the basis that their current behaviour is not autonomous because it is subject to forces that cause irrational choice, such as addiction. "Informed choice" in this sense is compatible with paternalism. This paternalism can be seen in public health policies such as deceptive advertising and the treatment of "bad habits" as addictions. Libertarians are bound to object to this. In the concluding section, however, it is suggested that public health can, nonetheless, find ethical succour from alternative approaches.